2017
DOI: 10.21475/ajcs.17.11.03.pne352
|View full text |Cite
|
Sign up to set email alerts
|

Quality of pelleted and bare lettuce seeds at different temperatures

Abstract: Two lettuce cultivars (Everglades and Virginia) were used to evaluate the performance of pelleted and bare seeds of lettuce under different germination temperatures. A completely randomized 2 x 2 x 5 factorial design was used. The factors consisted of two cultivars with pelleted and bare seeds, five intervals of germination temperatures (17 to 19ºC, 21 to 23°C, 25 to 28°C, 30 to 32°C, 34 to 38°C), with four replications. The first germination count, T50, germination, germination speed index, emergence, emergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(28 reference statements)
0
2
0
2
Order By: Relevance
“…Everglades is shown to be a cultivar with potential for use in tropicalized lettuce breeding programs. Almeida et al (2019), Catão et al (2018), Zuffo et al (2017), Catão et al (2016) and Catão et al (2014) analyzed the germination of the cultivar Everglades at 35 °C and reported that this cultivar, despite being tolerant to thermoinhibition, shows reduction in germination, but with less intensity compared to other cultivars. Gonai et al (2004) stated that the maximum temperature for lettuce seed germination depends on antagonistic interactions between the hormones gibberellin and abscisic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Everglades is shown to be a cultivar with potential for use in tropicalized lettuce breeding programs. Almeida et al (2019), Catão et al (2018), Zuffo et al (2017), Catão et al (2016) and Catão et al (2014) analyzed the germination of the cultivar Everglades at 35 °C and reported that this cultivar, despite being tolerant to thermoinhibition, shows reduction in germination, but with less intensity compared to other cultivars. Gonai et al (2004) stated that the maximum temperature for lettuce seed germination depends on antagonistic interactions between the hormones gibberellin and abscisic acid.…”
Section: Resultsmentioning
confidence: 99%
“…A resposta ao tratamento de sementes pode ser influenciada pelo genótipo da cultivar. Zuffo et al (2017) verificaram diferenças na germinação de sementes de cultivares de alface em função de tratamentos de peletização. No caso da pesquisa em questão, a cultivar Batavia Cacimba é do grupo classificado como alface-crespa roxa, diferente das demais, que são do grupo alface-crespa verde.…”
Section: Resultsunclassified
“…The action of temperature on the germination process has been reported by researchers for a great variety of species of vegetables (AMARO et al, 2014;CATÃO et al, 2014;NASCIMENTO et al,2016;SOARES et al, 2017). In lettuce seeds, for example, temperatures above 25 °C are known to cause decrease in physiological potential, reducing germination, germination speed, and water absorption, as well as biochemical reactions central to the successful germination of this species CANTLIFFE, 2002;ZUFFO et al, 2017). However, for species such as jambu, despise of growing relevance in Brazil, information concerning the effect of environmental variation on the germination process and development of A. oleracea, have yet to be properly elucidated, which impedes the use of reliable methods of physical and physiological analysis for the species, as well as limiting expansion of commercial production of the species.…”
Section: Introductionmentioning
confidence: 99%
“…A ação da temperatura sobre o processo germinativo tem sido reportada por pesquisadores em diferentes espécies de hortaliças (AMARO et al, 2014;CATÃO et al, 2014;NASCIMENTO et al, 2016;SOARES et al, 2017). Em sementes de alface, observa-se que temperaturas acima de 25 °C causam diminuição do potencial fisiológico, reduzindo a germinação, a velocidade de germinação, a absorção de água, bem como reações bioquímicas chaves ao processo germinativo dessa espécie CANTLIFFE, 2002;ZUFFO et al, 2017). Mas para espécies como o jambu, apesar de sua crescente relevância no Brasil, informações em relação ao seu processo germinativo e desenvolvimento, frente a variações ambientais, ainda não estão devidamente esclarecidas, o que impede a aplicação de métodos confiáveis de análises físicas e fisiológicas de sementes, limitando assim a expansão na produção da espécie.…”
unclassified